Accurate Dynamic Voltage and Frequency Scaling Measurement for Low-Power Microcontrollors in Wireless Sensor Networks. (November 2020) - Chéour, Rym; Khriji, Sabrine; Götz, Martin; Abid, Mohamed; Kanoun, Olfa
Abstract: Wireless Sensor Networks (WSNs) began to permeate all facets of life thanks to low cost, inherent intelligent-processing capability, simple installation, flexible networking and low energy consumption characteristics. Also, the evaluation of real-world applications on different platforms can solve the implementation problems and contribute to broadening the spectrum of Internet of Things (IoT) applications. The purpose of this paper is to reduce the microcontroller's average consumption of a wireless sensor node through architectural and design processes using advanced technologies. This paper provides a state-of-the-art investigation on the most up-to date Dynamic Voltage and Frequency Scaling (DVFS) techniques. A benchmark is given to choose the appropriate DVFS technique according to the type of component, the time and resources constraints, the application requirements, the expected performance level, etc. An energy-saving design is implemented using an ultra-low power microcontroller MSP430 and is based on the DVFS strategy. To efficiently quantify the consumed energy and to ensure more accuracy, a new concept is introduced, which is the normalized power to offer more accuracy. Real voltage/frequency scaling measurement were conducted. We show that a high voltage/frequency can lead to up to 57% increase of the normalized-power.